2018
DOI: 10.3390/molecules23071798
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pyrazole-Hydrazone Derivatives Containing an Isoxazole Moiety: Design, Synthesis, and Antiviral Activity

Abstract: In this study, a series of novel pyrazole-hydrazone derivatives containing an isoxazole moiety were synthesized. Antiviral bioassays indicated that some of the title compounds exhibited better in vivo antiviral activities against tobacco mosaic virus (TMV). In particular, compounds 6a, 6c and 6q exhibited the best curative activity, protection activity, and inactivation activity against TMV, respectively, which were superior to those of Ningnanmycin. This study demonstrated that this series of novel pyrazole-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…HCL. The reddish shiny 2-(3, 4-Dichloro-benzoyl)-benzoic acid crystals were appear [, , 51,52]. Step-3 Synthesis of 2-(3,4-Dichloro-benzoyl)-benzoic acid hydrazide Synthesis of 2-(3,4-Dichloro-benzoyl)-benzoic acid hydrazide from 2 2-(3,4-Dichloro-benzoyl)-benzoic acid ethyl ester with Hydrazine hydrate 99% in ethanol under reflux for 20-24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…HCL. The reddish shiny 2-(3, 4-Dichloro-benzoyl)-benzoic acid crystals were appear [, , 51,52]. Step-3 Synthesis of 2-(3,4-Dichloro-benzoyl)-benzoic acid hydrazide Synthesis of 2-(3,4-Dichloro-benzoyl)-benzoic acid hydrazide from 2 2-(3,4-Dichloro-benzoyl)-benzoic acid ethyl ester with Hydrazine hydrate 99% in ethanol under reflux for 20-24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, amide and their derivatives, which represented a key moiety in heterocyclic chemistry, played a leading role in pharmaceuticals and pesticides chemistry due to their potent bioactivities including antifungal, antibacterial, anticancer, antioxidant, and insecticidal activities. In our previous work, we had reported a series of novel isoxazole derivatives containing an amide moiety (Figure ) with potent antiviral activity against tobacco mosaic virus (TMV) …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, literature revealed that isoxazole-amide, an important scaffold for synthesis of various active molecules and their derivatives, had a wide range of biological activities, such as antifungal [4], herbicidal [4], antiviral [5], anticancer [6], antibacterial [7], and insecticide [8] activity. Meanwhile, literature revealed that acylhydrazone derivatives had a wide range of biological activities, such as antibacterial [9], fungicidal [10], insecticidal [11,12], and antiviral [13] activity.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, literature revealed that acylhydrazone derivatives had a wide range of biological activities, such as antibacterial [9], fungicidal [10], insecticidal [11,12], and antiviral [13] activity. Specifically, in our previous work, we reported a series of novel isoxazole-amide derivatives containing an acylhydrazone moiety (Figure 1) with potent antiviral activity against TMV [5]. In addition, the phenyl ring especially with electron-withdrawing groups, a privileged structure, represents a key motif in medicinal chemistry because of its ability to improve pharmacological activities including antiviral [14], antifungal [15], antibacterial [16,17], insecticidal [18], and nematicidal [17,19] activity.…”
Section: Introductionmentioning
confidence: 99%